2021
DOI: 10.1002/ange.202016013
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Oxythiophosphate Approaching the Good Balance with Wide Ultraviolet Transparency, Strong Second Harmonic Effect, and Large Birefringence

Abstract: Ultraviolet (UV) transparency, second harmonic effect and optical birefringence are three vital but mutually restrictive factors in the application of UV nonlinear optical (NLO) materials. It is difficult for traditional phosphates to achieve a good balance among these factors. In this communication, we propose that the structural evolution of the NLO motif from traditional phosphate to oxythiophosphate would enhance the birefringence and second harmonic generation (SHG) effect while maintaining wide UV transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Once parts of the ligands are replaced by another kind of anion, the broken symmetry induced by different anionic radii and electronegativities will result in large structural anisotropy as well as strong polarizability, which can simultaneously enhance the birefringence and SHG response of NLO crystals. This anion-mixing strategy has been applied to regulate the NLO performance in several ultraviolet (UV) NLO material systems functioned by BO x F 4– x , PO x F 4– x , PO x S 4– x , [NH 2 SO 3 ] − , [SO 2 (NH 2 ) 2 ], and SiO x N 4– x groups. However, the general significance of this strategy to optimize the performances of IR-NLO analogues has not been clarified yet due to the lack of a suitable material system with adjustable anionic compositions. …”
Section: Introductionmentioning
confidence: 99%
“…Once parts of the ligands are replaced by another kind of anion, the broken symmetry induced by different anionic radii and electronegativities will result in large structural anisotropy as well as strong polarizability, which can simultaneously enhance the birefringence and SHG response of NLO crystals. This anion-mixing strategy has been applied to regulate the NLO performance in several ultraviolet (UV) NLO material systems functioned by BO x F 4– x , PO x F 4– x , PO x S 4– x , [NH 2 SO 3 ] − , [SO 2 (NH 2 ) 2 ], and SiO x N 4– x groups. However, the general significance of this strategy to optimize the performances of IR-NLO analogues has not been clarified yet due to the lack of a suitable material system with adjustable anionic compositions. …”
Section: Introductionmentioning
confidence: 99%
“…27 In addition, the large birefringence in BaTiS 3 originates from the quasi-1D infinite chain of [TiS 3 ] ∞ , which indicates that the reduction of spatial dimension can also be used to enlarge the polarization anisotropy. 28 In recent years, more crystals with four-coordinated units, such as [BO x F 4−x ] (x = 0−4), 2,[29][30][31][32][33]39 [PO 3 F], 34−36 [PO x S 4−x ] (x = 0−4), 37 and [SiO x N 4−x ] (x = 0−4), 38,40 are reported to have enlarged birefringence when compared with their pure oxidized tetrahedra. This can be well-explained by the positive roles of F/N/S atoms on reducing the symmetry of original units to enhance the optical polarization anisotropy and birefringence.…”
Section: Introductionmentioning
confidence: 99%
“…9 The birefringence phenomenon comes from structural anisotropy inside crystals. 10,11 Therefore, there are many strategies to design new birefringent crystal materials, including: (1) introducing planar π-conjugated groups (e.g., [BO 3 ], [B 3 O 6 ], [C 3 N 3 O 3 ] and [NO 3 ]); typical examples are Li 6 Zn 3 (BO 3 ) 4 , 12 BaTi (BO 3 ) 2 , 13 Ba 2 Mg(BO 3 ) 2 , 14 Ba 2 Mg(B 3 O 6 ) 2 , 15 Na 3 Ba 2 (B 3 O 6 ) 2 F, 16 AZn 4 (OH) 4 19 Ba(NO 3 )Cl, 20 Cs 2 Pb(NO 3 ) 2 Br 2 , 21 23 and A(H 3 C 3 N 3 O 3 )(NO 3 ); 24 (2) incorporating heteroanionic tetrahedral groups, such as [BO x F 4−x ](x = 1-3), 25 [PO 3 F], 26,27 [PO 3 S], 28,29 and [SO 3 S]; 30,31 (3) adding d 0 metal cations with a second-order Jahn-Teller (SOJT) effect (e.g., Mo 6+ , V 5+ , and Nb 5+ ); [32][33][34] and (4) adding lone pair cations with stereoscopic activity (e.g., Sb 3+ , Pb 2+ , Sn 2+ , and Bi 3+ ). 33,[35][36][37] In recent years, it has been found that π-conjugated [C(NH 2 ) 3 ] cations exhibit greater anisotropic polarizability and larger second-order polarizability than [BO 3 ] units.…”
Section: Introductionmentioning
confidence: 99%